ANALYSIS OF THE EFFECTIVENESS OF CRITICAL PATH METHOD IMPLEMENTATION IN FLOOD CONTROL CONSTRUCTION PROJECTS (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Effective control of time and cost performance remains a persistent challenge in river embankment development projects, which are characterized by linear construction processes, environmental uncertainty, and high exposure to schedule disruption. Although construction management techniques such as the Critical Path Method (CPM) and Earned Value Management (EVM) are widely applied, empirical evidence on their integrated effectiveness in flood control infrastructure remains limited. This study aims to evaluate the effectiveness of construction management techniques in controlling time and cost performance in river embankment development projects and to explain the underlying causes of performance deviations. The research adopts a quantitative analytical case study approach, utilizing CPM and EVM to analyze baseline schedules, actual progress, and cost data. The findings reveal persistent schedule delays and moderate cost inefficiencies, with critical activities exerting a dominant influence on overall project performance. Schedule slippage was identified as the primary driver of cost escalation, while the effectiveness of CPM and EVM was constrained by static application and delayed managerial response. The study concludes that construction management techniques are effective as diagnostic tools but require adaptive and integrated implementation to function as proactive control mechanisms. This research contributes theoretically by contextualizing CPM–EVM integration within river embankment projects and practically by providing evidence-based insights for improving time and cost control in flood control infrastructure.